(untitled) (Journal of Fiber Bioengineering and Informatics, 2023)
A common phase change material (PCM) utilized for thermal energy storage is paraffin wax (PW). However, the applicability and thermal energy storage effectiveness of PW are constrained by its leakage and poor thermal conductivity. By using the melting-blending technique, composites of PW and expanded graphite (EG) were created, and investigations into the morphology and thermal behavior of PW/EG composites were conducted. in this study. It was found that PW was used as a coating to cover the EG structure and no leakage was detected. The final PW/EG composites had the latent heat of fusion around 122 J/g. Additionally, the embedded PW in EG had a higher degree of crystalline growth. We propose that PW/EG composites have significant potential in thermodynamics-related fields.